Aging impairs osteoblast differentiation of mesenchymal stem cells grown on titanium by favoring adipogenesis - ABUNA, Rodrigo Paolo Flores (J Appl Oral Sci, 2016)
Aging negatively affects bone/titanium implant interactions. Our hypothesis is that the unbalance between osteogenesis and adipogenesis induced by aging may be involved in this phenomenon. OBJECTIVE: We investigated the osteoblast and adipocyte differentiation of mesenchymal stem cells (MSCs) from young and aged rats cultured on Ti. MATERIAL AND METHODS: Bone marrow MSCs derived from 1-month and 21-month rats were cultured on Ti discs under osteogenic conditions for periods of up to 21 days and osteoblast and adipocyte markers were evaluated. RESULTS: Cell proliferation, alkaline phosphatase (ALP) activity, extracellular matrix mineralization and gene expression of RUNX2, osterix, ALP, bone sialoprotein, osteopontin, and osteocalcin were reduced in cultures of 21-month rats compared with 1-month rats grown on Ti. Gene expression of PPAR-γ , adipocyte protein 2, and resistin and lipid accumulation were increased in cultures of 21-month rats compared with 1-month rats grown on the same conditions. CONCLUSIONS: These results indicate that the lower osteogenic potential of MSCs derived from aged rats compared with young rats goes along with the higher adipogenic potential in cultures grown on Ti surface. This unbalance between osteoblast and adipocyte differentiation should be considered in dental implant therapy to the elderly population.